Characterization of the complete chloroplast genome of Paederia scandens (Rubiaceae): a Chinese folk medicinal plant. Issue 2 (3rd July 2019) - Li, Zheng-Hui; Ye, Ke; Lv, Xiao; Zhang, Xian; Ling, Li-Zhen; Ai, Hong-Lian; Zhang, Shu-Dong
Abstract: Paederia scandens has been used as a traditional medicine in Asian countries to treat jaundice, dysentery, and the pain of rheumatism. The complete chloroplast (cp) genome sequence of P. scandens was reported and characterized in this study. The cp genome is 153, 626 bp in length, composed of a pair of 26, 513 bp inverted repeat (IR) regions separated by a large single-copy (LSC) region of 83, 712 bp and a small single-copy (SSC) region of 16, 888 bp. There were 131 predicted genes (86 protein-coding genes, 37 tRNA genes, and 8 rRNA genes) in the genome, and the overall GC content of the genome is 37.7%. Phylogenetic analysis based on the cp genome data showed that P. scandens was sister to the clade formed by Galium mollugo and G. aparine .